Issues concerning Social Security, Medicare and the national debt - Paul F. Gentle (Health Economics and Management Review)
It happens quite usually that national politicians can regularly speak of limiting Social Security and Medicare in some ways. However, when confronted with enough public scrutiny in general, those politicians who advocate such reductions become less strident in their own comments. Taxes from the Federal Insurance Contributions Act (FICA) provides revenue for the Social Security and Medicare programs. The amount of gathered tax revenue is partially dependent on the payroll FICA tax cap. This article explains how the cap works. Social Security started in 1935, as part of the New Deal. In 1956, insurance to aid disabled people was started. In this article, different aspects of that cap are also examined. In 1965, the Medicare program came into effect. Any temporary surplus of federal funds must be used to hold US Treasury Securities. Starting in Fiscal Year 1969, the United States of America have operated under the law of the Unified Budget Act. This act stipulates that all receipts and outlays of all federal spending be consolidated into a unified budget. Much of these funds will be needed as future retirees receive benefits from the Social Security and Medicare. As that happens, there may be comparatively less US Treasury securities held by the Social Security and Medicare Trust funds. This article shows some of the concerns that the President and Congress face in budget negotiations. In 2017, the rating for long-term US Treasury Securities stayed at AA+ by Standard and Poor’s, a credit rating firm. Both Congress and the US President needed to work together to slow the growth of annual deficits, which adds to the federal debt. Interestingly, two other bond rating firms, Moody’s Investors and Fitch, maintained the bond rating of AAA. It has to be remembered that none of these ratings are permanent. As time goes on, firms that give bonds ratings will keep on analysing those who issues securities, including the US government. Furthermore, not all credit rating agencies agreed with any fall of the credit rating. As to a more recent credit rating, US Treasuries were rated at AAA. The reader should always be cognizant of the fact that ratings can change over time. Such times as occurred in May 2023 (debt ceilings, tax revenues and spending disagreements between the legislative and executive branches) may or may not be contemplated regarding the credit rating of US Treasuries.